Numerical simulation of slamming load and fluid splashing characteristics of scientific research vessels under extreme sea conditions - Shixian WU; Minzhan HUANG; Jiadong YIN; Xuan MEI; Minli ZHOU; Pengnan SUN (Zhongguo Jianchuan Yanjiu)
ObjectiveScientific research vessels may encounter extreme sea conditions during research voyages. It is of great significance to study the slamming load and fluid splashing characteristics of scientific research vessels under extreme sea conditions to ensure the safety of scientific personnel and the performance of scientific equipment. MethodsThe article takes the Sun Yat-sen University scientific research vessel as an example, based on the smoothed particle hydrodynamics (SPH) method, establishes a δ-SPH and fluid structure coupling dynamic model, and carries out SPH numerical simulation of the scientific research vessel encountering extreme sea conditions. It predicts the slamming load, the degree of deck wetness and fluid splashing under extreme sea conditions, and analyzes its influencing factors and physical mechanisms.ResultsThe results indicate that as the wave height increases and the wavelength approaches the captain, the slamming load on the hull increases, and the degree of deck wetness and fluid splashing becomes more significant. ConclusionThe results provide a basis for maneuvering and controlling scientific research vessels under extreme sea conditions, ensuring the safety of personnel and equipment performance on scientific research vessels.